Prevalence and Patterns of Back Pain Complaints among Pregnant Woman in Developing Countries in Asia: A Literature Review - Wanti, Qori Karunia; Fatmarizka, Tiara (Academic Physiotherapy Conference Proceeding, 2022)
Introduction: Back pain has become one of the most common and serious musculoskeletal symptoms. About 5% of those symptoms require medical treatment. Back pain is generally complained of in the II to III trimester of the n's perception. This is due to the effects of musculoskeletal changes, namely an increase in the load on the vertebrae due to the growth of the fetus that is getting bigger. The occurrence of back pain during pregnancy is closely related to various patterns of pain in the back, including low back pain, pelvic girdle pain, and combination pain. In the lower middle and lower middle regions, especially Asia, they still often face challenges related to poor health and the economy, as well as a lack of knowledge about the problem of back pain during pregnancy. This is important to know so that it becomes an effort if back pain arises in pregnant women and can be handled properly.Objective: To find out the prevalence and how the pattern of back pain experienced by pregnant women changes.Methods: This study used a literature review design. Usually, risk assessment is done using the Joanna Briggs Institute (JBI) Critical Appraisal Score.Results: The results of this study found that back pain is often reduced during the III trimester of pregnancy, which can be affected by increasing gestational age, jobs, and pregnant women who have a history of pain. The pain patterns found were low back pain (LBP) as much as 3%–86%, pelvic girdle pain (PGP) by 2%–37%, and combo pain by 22%–42%.Conclusion: The prevalence of back pain in developing countries, especially the Asian region, showed the most LBP complaint patterns with a percentage of 3%–86% of the total 2,334 respondents who experienced back pain during the third trimester of pregnancy.